Ā. Na. Ma. Bajalura Raśīda 1911-1986 - Bisb́āsa, Sukumāra (Bāṃlā Ekādemī, 1990)
On the life and works of Ā. Na. Ma. Bajalula Raśīda 1911-1986
Biographie des bengalischen Schriftstellers Bajalula Raśīda
Keywords: Bajalura Raśīda; Ā. Na. Ma; Authors; Bengali